Histopathological Profile of Wistar Rat Kidney in High-Fat Diet Model Treated with a Combination of Tea and Mango Mistletoe Extracts - Rianda Siwi Cholida; Nour Athiroh Abdoes Sjakoer; Ari Hayati (Biology, Medicine, & Natural Product Chemistry, 2026)
A high-fat diet (HFD) can cause kidney damage through oxidative stress and inflammation. This study aimed to analyze the histopathology of the kidneys in rats given HFD after administering a combination of tea mistletoe leaf extract (Scurrula atropurpurea) and mango mistletoe (Dendrophthoe pentandra) (MESA-DP). Using a randomized pretest-posttest control group design, the rats were divided into a negative control group (G1), an HFD control group (G2), and three treatment groups with combined doses of MESA-DP: 50, 100, and 200 mg/kg body weight (G3, G4, G5). During the 37-day treatment period, microscopic examinations were conducted. The results showed that (G2) experienced an increase in fat accumulation (12%) and glomerulus diameter (1783.1 micrometer), compared to G1 (6%; 1507.5 micrometer). G3 actually worsened the condition (22%; 2003.1 micrometer). G4 successfully reduced fat accumulation to 9% and glomerulus diameter to 1689.4 micrometer, while G5 approached normal levels (7%; 1674.4 micrometer). ANOVA tests on the kidney fat area and glomerulus diameter showed p=0.018 (p